Synthesis and Characterization of LTC x(Ni0.90Mg0.10)Fe2O4–(1−x) (Ba0.88Sr0.10Ca0.02)(Ti0.95Zr0.05)O3 Ceramic Composites for Antenna Application - Hossain S.S.; Shekhawat D.; Roy P.K. (My University, 2025)
The objective of the work is to synthesize low-temperature co-fired (LTC) biphasic ceramic composites of dielectric (Ba0.88Sr0.10Ca0.02)(Ti0.95Zr0.05)O3 and spinel ferrite (Ni0.90Mg0.10)Fe2O4 with different fractions by a standard ceramic route and to study the effects on physical, magnetic, dielectric and electrical properties for antenna application. The respective ferrite and dielectric powders are prepared by two different techniques, i.e., sol–gel auto combustion and solid–state route, respectively. Dielectric-ferrite mixed powder is pressed into pellets and toroids by uniaxial pressure, and the pellets are sintered at 950 °C. The X-ray diffraction (XRD) & FTIR analysis disclose the coexisting of perovskite and spinel phases in the composite without interacting with each other. The SEM analysis displays a compact structure with few porosities. The changes in dielectric constant and loss tangent of composite specimens with frequency are also investigated. The dielectric constant is continuously increased, and permeability is decreased with increasing dielectric content. Observations of M-H hysteresis loops and dielectric measurements support the magnetic and dielectric nature of the composite specimens. The magnetoelectric voltage coefficient is confirmed to monitor the interaction between magnetic and dielectric phases. The high-performance composites are useful for antenna applications as they have almost equal permittivity and permeability. © 2023, The Korean Institute of Electrical and Electronic Material Engineers.